Mengamati Perkembangan Remaja Kelas 3 SMA: Hasil Wawancara dan Analisis - Ramadhan Lubis; Mozaiva Piandra; Dhafiyah Azzahra; Izhar Isna Karimah; Fannya Dwi Martani Wijaya; Sarah Pebriyanti (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
Seventeen is a crucial age in adolescent development, marked by various psychological, social, and cognitive changes. According to Erikson, adolescents at this stage face the psychosocial crisis of “identity versus role confusion,“where they begin to form a sense of self. Piaget explains that they enter the formal operational stage, where abstract and logical thinking emerge. Monks et al. further emphasize that adolescent development is strongly influenced by social interactions with family, peers, and the school environment. This study aims to explore the psychological development dynamics of 17-year-old adolescents and the influencing factors such as family environment, academic pressure, and social relationships. The research uses a qualitative case study method involving one twelfth-grade high school students. The findings reveal that adolescents at this age begin to show a more stable identity, greater independence, and reflective thinking abilities. However, some also experience anxiety, identity conflicts, and social pressure. These findings highlight the importance of emotional support from both families and schools in guiding adolescents through this transitional stage in a healthy and adaptive way.